The Therapeutic Value of Green Tea in Preventing the Negative Effects of Methotrexate on the Stomach - A. Ali, Ali Hassan (Asian Journal of Pharmaceutics (AJP), 2024)
Aim: The purpose of the study was to determine how green tea contributed to the adverse effects on the stomach that methotrexate (MTX) mediated. Materials and Methods: Sixty adult male albino rats were split equally into three groups. The first group received intraperitoneal injections of normal saline twice a week for 9 weeks at a dosage of 0.5 mg/kg body weight. For 9 weeks, the second group received intraperitoneal injections of MTX hydrate at a dosage of 0.5 mg/kg body weight twice a week. The third group, on the other hand, was given green tea and MTX at an oral dosage of 36 mg/kg body weight/day in 0.2 mL distilled water for an additional 9 weeks. The stomachs of the sacrificed animals were processed, stained, and viewed under a microscope. Then, serum sample concentrations of interleukin (IL)-2 and IL-6 as well as glutathione peroxidase (GPx), glutathione (GSH), and superoxide dismutase (SOD) were measured. Results and Discussion: The histological findings demonstrated that green tea can significantly reverse the pathological alterations caused by MTX, which damages stomach tissue. Furthermore, green tea therapy exacerbated MTX-induced reductions in GSH content, GPx, and SOD activity and dramatically decreased the elevation of serum MDA, IL-2, and IL-6 contents that MTX had caused. Conclusion: Our findings suggest that green tea can moderately protect histological damage of the stomach in rats exposed to MTX, as well as reduce pro-inflammatory parameters and oxidative stress.